Comparison of three‐dimensional high‐resolution manometry and endoanal ultrasound in the diagnosis of anal sphincter defects. (24th October 2013) - Vitton, V.; Ben Hadj Amor, W.; Baumstarck, K.; Behr, M.; Bouvier, M.; Grimaud, J.‐C.
Abstract: Aim: Three‐dimensional high‐resolution anorectal manometry (3D HRAM) is a new technique that can simultaneously provide physiological and topographical data. Our aim was to assess whether it can identify anal sphincter defects by comparing it with endoanal ultrasonography (EUS) considered as the gold standard. Method: An anal defect on 3D HRAM was defined as a continuous circumferential area over which the pressure was < 10 mmHg during the measurement of anal resting and voluntary contraction pressure. Inter‐observer agreement was also assessed. Results: A total of 100 patients (93 females) with a mean age of 53.5 ± 15.3 years were included. The positive diagnosis of an anal sphincter defect using 3D HRAM and EUS was in agreement (59.3%) ( κ  = 0.419) of the time for the internal anal sphincter (IAS) and (55.9%) ( κ  = 0.461) for the external anal sphincter (EAS). The inter‐observer agreement for a diagnosis of an anal sphincter defect was (100%) ( κ  = 0.937) for the IAS and (95%) ( κ  = 0.751) for the EAS. The intra‐class correlation coefficient for the extent of the defect was 0.853 for the IAS and 0.651 for the EAS. Conclusion: The preliminary results demonstrate some level of agreement in the diagnosis of anal sphincter defects between 3D HRAM and EUS but insufficient for 3D HRAM to be adequately reliable using the criteria chosen. The excellent inter‐observer agreement, however, demonstrates that 3D HRAM is reproducible and provides a new dimension for the evaluation of sphincter function.